Management of benign primary vertebral tumors: WFNS spine committee recommendations - Francesco Costa; Francesco Restelli; Niccolò Innocenti; Corinna Zygourakis; Zan Chen; Mirza Pojskic; Onur Yaman; Artem Gushcha; Salman Sharif; Mehmet Zileli (Interdisciplinary Neurosurgery)
Background: Benign primary vertebral tumors (PVTs) represent a diverse group of spinal lesions that, despite their non-malignant nature, can significantly impact patients’ quality of life. This review aimed to formulate the most current, evidence-based recommendations regarding the management strategies for benign PVTs. Methods: To this aim, comprehensive search was conducted in PubMed/EMBASE/MEDLINE databases. Inclusion criteria included English-language publications between January 2012 and December 2023. The screening process involved reviewing abstracts, assessing full-text articles, and reviewing reference lists for additional studies. Eligibility criteria were applied to ensure the selection of relevant studies. Data extraction involved recording various variables. A total of 160 abstracts were screened, resulting in 99 articles being selected for further review. 57 articles met the inclusion criteria and were included in the study. The results were discussed and voted in two consensus meetings of the WFNS (World Federation of Neurosurgical Societies) Spine Committee, reaching a positive or negative consensus using the Delphi method. Results: Imaging with MRI/CT is essential for diagnosis and treatment planning, with classification systems guiding surgical strategies; general condition, tumor histology, and life expectancy must be considered. En-bloc resection is the gold standard for malignant tumors, while vertebroplasty, radiotherapy, or minimally invasive ablation may be appropriate depending on lesion type. Specific management recommendations were confirmed for osteoid osteoma, osteoblastoma, ABCs, giant cell tumors, and hemangiomas, including the role of embolization, biopsy, and emerging percutaneous procedures. Conclusions: The WFNS Spine Committee finalized multiple recommendation guidelines on the management of benign primary vertebral tumors. Further higher-quality studies are recommended to establish more substantial evidence and recommendations.